Effectiveness of Promotional Advertisements by Jatim Park 3 on Instagram Social Media - Andita Rista Amelia Wardani; Yuswanti Ariani Wirahayu (LP3M Universitas Putra Bangsa, 2025)
The existence of various emerging tours with interesting concepts and competing to attract tourists has further increased competition in the industry. One form of competition is through the intensive promotion of tourist objects. Jatim Park 3 was chosen in this research because as an artificial tourist attraction, this tourist attraction is generally considered quite vigorous and active in promotion on social media, especially Instagram. The research method used in this research is a quantitative descriptive analysis method. The collection techniques used include distributing questionnaires, observation, and literature study with data processing using the EPIC model method. The EPIC rate results obtained from all dimensions were 4.15. This value falls into the effective scale range. It can be seen that the level of effectiveness of Jatim Park 3's promotion via social media and Instagram is effective. The lowest score on the EPIC dimension is the empathy dimension of 3.96. Furthermore, visitor characteristics regarding regional origin are dominated by East Java as much as 64%. In terms of age characteristics, the age range that dominates coming to Jatim Park 3 is the productive age group, namely 20-24 years with a percentage of 45%.